Diversity, biogeography and conservation of freshwater mussels (Bivalvia: Unionida) in East and Southeast Asia - Zieritz, Alexandra (2018)
Recent research efforts have significantly advanced our knowledge on Asian freshwater mussel (Bivalvia: Unionida) diversity and distribution. Here we provide a modern consensus of the diversity, biogeography and conservation of Unionida in the region comprising East and Southeast Asia (excluding Wallacea) and Asian Russia. A data review confirmed the presence of 228 native and 3 non-native Unionida (98% Unionidae, 2% Margaritiferidae), rendering the region a global hotspot of freshwater mussel diversity. Species richness was highest in China (particularly Yangtze basin) in absolute numbers and Cambodia when correcting for country area, and decreased gradually towards the south and steeply towards the north and east. Six of the seven unionid subfamilies are native to the region, with species richness peaking in Southeast Asia for Rectidentinae, Gonideinae, Parreysiinae and Modellnaiinae, China for Anodontinae and Unioninae, and Asian Russia for Margaritiferidae. Conservation status and data collected after 1980 were not available for 61 and 24% of species, respectively. Dams, deforestation and pollution are likely the major threats to mussels in the region, though data in this respect are scarce. The Philippines, Laos, Indonesia, Myanmar and Malaysia are among the countries with the poorest data availability and urgently require research.